2002
DOI: 10.1051/0004-6361:20011622
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of the finite horizontal extent of the optical turbulence layers. Implications for new adaptive optics techniques

Abstract: profiles measured (almost simultaneously) by a GS along different lines of sight. The results of this study show that (1) the horizontal size of the turbulent layers can be finite, (2) the simulations and the measurements are well correlated and (3) for the first time, we show that the model can reproduce observed seeing values that vary as much as 0.50 during the same night. This definitely shows that the numerical simulations are a useful tool in the context of the turbulence characterization for astronomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…It has been shown previously that such dependences can exist 29 and some preliminary investigation for Mauna Kea 13N using TMT data were done. It turns out that the TMT data do not cover a sufficiently large range of zenith and azimuth angles for this purpose and that, ideally, simultaneous measurements with several instruments pointing in different directions should be used.…”
Section: Higher Resolution Profilesmentioning
confidence: 90%
“…It has been shown previously that such dependences can exist 29 and some preliminary investigation for Mauna Kea 13N using TMT data were done. It turns out that the TMT data do not cover a sufficiently large range of zenith and azimuth angles for this purpose and that, ideally, simultaneous measurements with several instruments pointing in different directions should be used.…”
Section: Higher Resolution Profilesmentioning
confidence: 90%
“…We imagine that we h a ve a GCM model extended over the whole globe and having a horizontal resolution of about 100 km. We cut a domain in a region around a telescope having an extent of the order of a few tens of kilometers and a horizontal resolution of about 500 m: this is our orographic model (see for example Fig.1 in Masciadri et al 25 ).…”
Section: Methods For Simulating the Optical Turbulencementioning
confidence: 99%
“…How can we estimate, in the best way, the P and P parameters ? 16 ). 10 nights of measurements provided by a GS and balloons were considered.…”
Section: Score Of Success Of the Numerical Techniquementioning
confidence: 99%
“…Echevarría et al (1998) reported a median open air seeing of 0.61 arcsec, obtained during an extensive (3-years) seeing campaign, using non-differential seeing monitors. Masciadri et al (2002) presented evidence of a finite horizontal extension of turbulence layers at the site.…”
Section: The Observatory Sitementioning
confidence: 97%